Sources and Extent of Stress as Perceived By the Faculty Members in TwoAgricultural Colleges in Karnataka- A Study (Indian Journal of Extension Education, 2010)
It has been stated that psychologists have not only studied ‘stress’, they have elevated the issue of ’stress’ as an area of concern to the public. However, in doing so they have faced the problem of being able to succinctly and consistently define what stress actually is. Despite the growing volume of literature on the subject, it is thought by some psychologists that ‘stress’ does not actually exist. When one has reviewed some of this literature, it is possible to understand why they might hold this position. The term ’stress’ is, unfortunately, an imprecise term at best. Stress is common to every human being. There is no exception for anyone whether he is a small labor or a big businessperson. Stress is common and more at working condition. It may be because external environment, organizational climate, persons commitment toward organizational rules and regulations and also psychological factors. Stress is a common problem that affects almost all of us at some point in our lives. Learning to identify when you are under stress, what is stressing you, and different ways of coping with stress can greatly improve both your mental and physical well-being. As Hans Selye (1956), the noted stress researcher, once said, "Stress is a scientific concept which has suffered from the mixed blessing of being too well known and too little understood."